WELFARE IN PUBLIC POLICIES - Paixão, Hildeberto Pedro; de Souza, Alexandra Aparecida Borges; Broering, Geovani; Rodrigues, Renato (Seven Editora, 2026)
This article analyzes the phenomenon of welfare assistance within the context of Brazilian public policies, discussing its relationship with social assistance, the role of the State, and its social and economic impacts. The study begins by distinguishing between welfare assistance and social assistance, highlighting that the former has an emergency and palliative character, whereas social assistance constitutes a right guaranteed by the 1988 Brazilian Constitution and is part of the social security system. The research is exploratory and bibliographical in nature, based on theoretical contributions from sociology, political economy, and social theory, as well as the analysis of public policies implemented in Brazil, such as conditional cash transfer programs and the Unified Health System. Institutional data and local experiences in social policy are also discussed, including references to the municipality of Lages, Santa Catarina. The results indicate that although income transfer programs contribute to reducing poverty and social vulnerability, their effectiveness depends on their articulation with structural policies related to economic development, education, and productive inclusion. It is concluded that public policies based on social rights can play an important role in promoting citizenship and reducing social inequalities.